ZIKIR HENING SUFI DALAM ANALISIS SEMIOTIKA - Hasanuddin Chaer; Ahmad Sirulhaq; Abdul Rasyad (Syifa al-Qulub, 2020)
The Sufis are practitioners of the science of purification of heart. Sufism is the esoteric or inner dimension of Islam. Sufism can’t to be explained theoretically, it can only be understood through participation and practice. The activities of the ritual dhikr of Sufi have signs and meanings. The Sign of systems include words, movements, pictures, numbers, and objects. These signs have meaning to convey. The Signs have denotative and connotative of meanings.This article uses a descriptive analysis method. We analyze discursive and non-discursive symbols, is words that involve emotions and non-verbal meanings such as Sufi body movements in ritual prayers and dhikr. Dhikr “silence” is a command to observe silence which is the purpose of dhikr silent. The purpose of this article is to open the essence of Sufi and semiotics of tasawwuf as the deepest spiritual teachings of the Prophet Muhammad in achieving of silence of “qolbu mu’min Baitullah”